The Effect of Earnings Management and Tax Planning on Firm Value Moderated by Earnings Persistence - ARDIANSYAH, Fery; HIDAYAH, Nurul (Journal of Governance, Taxation and Auditing, 2025)
This study examines the effect of earnings management and tax planning on firm value, with earnings persistence as a moderating variable, in consumer non-cyclical companies listed on the Indonesia Stock Exchange during 2020–2024. Using a quantitative observational design, the research is based on secondary data from annual financial statements, comprising 113 observations selected through purposive sampling. Earnings management was measured by the Modified Jones Model, tax planning by the Effective Tax Rate (ETR), firm value by Tobin’s Q, and earnings persistence by changes in pre-tax income relative to total assets. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS 26. The results reveal that both earnings management and tax planning significantly and negatively affect firm value, while earnings persistence has no significant effect and fails to moderate these relationships. The study’s novelty lies in employing earnings persistence as a moderating variable, which enriches the existing literature on firm value determinants. These findings reinforce signaling theory, suggesting that opportunistic managerial practices diminish market perception. The implications offer valuable insights for managers, investors, and regulators in assessing financial reporting quality and corporate governance.